2020
DOI: 10.1038/s41598-020-62552-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lag phase can be indicative of, or independent from, cellular stress

Abstract: Measures of microbial growth, used as indicators of cellular stress, are sometimes quantified at a single time-point. in reality, these measurements are compound representations of length of lag, exponential growth-rate, and other factors. Here, we investigate whether length of lag phase can act as a proxy for stress, using a number of model systems (Aspergillus penicillioides; Bacillus subtilis; Escherichia coli; Eurotium amstelodami, E. echinulatum, E. halophilicum, and e. repens; Mrakia frigida; Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 125 publications
2
48
0
3
Order By: Relevance
“…In contrast, none of the low-molecular-weight chitodextrin oligomers, (GlcNAc) 2-6 , was detected. The presence of the ectosymbiont in a coculture slightly prolonged the growth lag phase of the host, a phenomenon that implies an adaptation period although not necessarily (biotic or abiotic) stress (38). Indeed, neither the maximum specific growth rates (0.028 to 0.035 h −1 ) nor the yield of the host biomass were affected (Fig.…”
Section: Physicochemical Properties and Archaeal Composition Of The Cmentioning
confidence: 97%
“…In contrast, none of the low-molecular-weight chitodextrin oligomers, (GlcNAc) 2-6 , was detected. The presence of the ectosymbiont in a coculture slightly prolonged the growth lag phase of the host, a phenomenon that implies an adaptation period although not necessarily (biotic or abiotic) stress (38). Indeed, neither the maximum specific growth rates (0.028 to 0.035 h −1 ) nor the yield of the host biomass were affected (Fig.…”
Section: Physicochemical Properties and Archaeal Composition Of The Cmentioning
confidence: 97%
“…By the addition of glucose + yeast extract, the lag phase of growing microorganisms shortened irrespective of the initial nutrient content (Table 2), reflecting an advanced adaptation to the newly available resources, fueling a balanced, and less stressed metabolic network (Hamill et al, 2020). However, the substrate turnover time of C-, N-, and P-cycling extracellular enzymes during lag phase and exponential growth of microorganisms was stable in nutrient-rich soil, whereas the substrate turnover time of enzymes was strongly shortened in nutrient-poor soil (Figure 8).…”
Section: Microbial Growth After Substrate Addition In Contrasting Formentioning
confidence: 99%
“…These growth curves show different phases of microbial growth, namely (1) lag, (2) exponential, (3) stationary and 4) death phase (Figure 1). In general, the lag phase metabolism may include the activation of signaling pathways and specific transcriptional changes which might lead to the upregulation of protein assembly, nucleotide metabolism, lipopolysaccharide biosynthesis, respiration, and other processes which are needed for differentiation and multiplication (Hamill et al, 2020). These processes occur during lag phase, initiate exponential growth and cell divisions (Panikov, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…After the end of the ALE experiment, we assessed an effect of 2M KCl-induced osmotic stress on the growth phenotype of the analyzed strains by using a spot test assay, which is a standard method to evaluate the growth phenotype [35][36][37]. We showed that KCl-evolved derivatives of strains 2 and 3 (2_KCl_a, 2_KCl_b as well as 3_KCl_a, and 3_KCl_b, respectively) significantly increased their fitness to high osmotic pressure.…”
Section: Kcl-ale-based Improvement Of Wine Yeasts' Tolerance To Osmotmentioning
confidence: 99%
“…In fact, there are several reports showing that the mRNAs of genes engaged in the stress response are regulated differently in comparison to other [50,51]. Examples include the upregulation of synthesis, the extension of the transcript half-lives [36], and finally selective mRNAs stabilization (or degradation) that, in turn, are dependent on the stress response phase [51].…”
Section: Adaptive Evolution-mediated Changes In Glycerol Concentrationsmentioning
confidence: 99%